Fabricating a hollow bulb obturator - Ali Tunçdemir; Fatih Sari (Cumhuriyet University, 2013)
Obturators are generally used in the rehabilitation of the maxillectomy defects. Ideally, obturators should be light, properly fit and construction should be made easily. By decreasing the weight of the prosthesis, the retention and stability may be optimized to allow the obturator for function comfortably during mastication, phonation, and deglutition. In this case, a 65-year-old male patient underwent surgical removal of left part of the maxilla due to the squamous cell carcinoma. In this technique fabrication of a hollow bulb obturator prosthesis as a single unit in heat-cured acrylic resin using a single-step flasking procedure was described. The patient's functional and esthetic expectations were satisfied.